2016
DOI: 10.1515/biolog-2016-0123
|View full text |Cite
|
Sign up to set email alerts
|

Sexual size monomorphism and body variation in the fat dormouse Glis glis in Slovakia

Abstract: Sexual size dimorphism (SSD) of the fat dormouse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In this study, there were no significant differences in body mass between females and males, which was in accordance with findings reported by [ 59 ]. Both studies confirm the research of [ 60 ], who demonstrated sexual size monomorphism. Authors believe that the lack of sexual size dimorphism can be beneficial in the inter- and intra-sexual interaction, which may relate to passive mate-guarding.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, there were no significant differences in body mass between females and males, which was in accordance with findings reported by [ 59 ]. Both studies confirm the research of [ 60 ], who demonstrated sexual size monomorphism. Authors believe that the lack of sexual size dimorphism can be beneficial in the inter- and intra-sexual interaction, which may relate to passive mate-guarding.…”
Section: Discussionsupporting
confidence: 92%
“…This strategy consists of maximizing the number of offspring of variable weights with the aim of maximizing fitness when environments vary temporally [100,101]. No differences in offspring weights between sexes were found in any of the three age groups considered, although they were not expected because previous findings documented an overall non-significant difference in morphometric traits (including body weight) between sexes in this species [60,102,103]. In this vein, the use of standardized age categories based on external characters [76] that could be independent of the weight-which can be affected by environmental factors affecting pup development-could be advisable for comparative purposes in monitoring schemes.…”
Section: Discussionmentioning
confidence: 99%
“…Analysing the relationship between rodent, including some root vole sub-species, body weight and their cranial or body traits has been a widely used approach in order to estimate body weight and biomass of mammals consumed by predators [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Borowski et al [ 25 ] investigated the relationships between the biometrics of cranial traits and the body weight of Alexandromys oeconomus stimmingi , while Balčiauskas and Balčiauskiené [ 27 ] estimated body weight from 26 cranial and pelvic features of A. oeconomus stimmingi .…”
Section: Introductionmentioning
confidence: 99%